(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
In this article, the research on Tikuna Amerindian masks, located on the triple border between Brazil, Colombia and Peru, will be addressed. It is a theoretical-practical research, using the methodology of autoetnographic research, where the artist’s gaze is evident. So, from my coexistence with the Tikuna, in the village (in Nossa Senhora de Nazaré, AM) and in an urban context (in Parque das Tribos, Manaus) I will talk about this universe of masks that are part of the main Tikuna ritual, of female initiation Worecü, The Feast of the Young Girl, which happens when the girl Tikuna has her menarche.